Simile in English: from description to translation - Pierini, Patrizia (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Simile is much less investigated than metaphor, although it occurs as frequently in discourse. This paper aims to provide an account of similes in English, which serves as the starting point for an exploration of the problems they can pose when translated into Italian. First, it deals with the nature and function of similes, the criteria for their classification, and their interpretation. Then, it examines a range of similes illustrating the translation problems they can pose, and discusses the strategies to adopt for each problem stated. The data discussed are taken from English texts belonging to various textual genres, and their translations into Italian.